Comparison of HPLC with Tinia for HbA1c measurement in diabetic and non-diabetic patient; a study from a tertiary care hospital of Baluchistan - Ahmed, Azeema; Bashir, Saima; Ayub, Zeeshan; Ahsan, Javaria; Iqbal, Hamid (International Journal of Pathology, 2024)
Background: Diabetes mellitus, a disease with serious implications on human health ,is on continuous rise. It is the need of hour to find and establish the markers to measure its long term effects. Diabetes Control and Complication Trial has confirmed role of HbA1c in effective blood glucose level monitoring .New methods are being developed for measurement of HbA1c .Before using these methods, it is essential to analyze these methods for reliability .Therefore in our study we will compare and evaluate correlation and agreement between Turbidimetric Inhibition Immunoassay TINIA and High Performance Liquid Chromatography (HPLC) for Glycated Hemoglobin A1c (HbA1c) measurement.Methods: Three hundred and ninety-four samples were analyzed simultaneously on Roche Cobas 501 and D-10 HbA1c analyzer by Bio-Rad for HbA1c level estimation. The results were entered into SPSS version 26 for method validation. This is an observational study conducted at Department of Pathology Combined Military Hospital (CMH) Quetta from January 2022 to August 2023.Results: Inter and intra run coefficient of variation (CV) was within the allowable limit of 2 %. Mean difference between results of Turbidimetric Inhibition Immunoassay TINIA and High-Performance Liquid Chromatography HPLC was very low with HPLC results slightly on higher side. For low control TINIA had between run CV of 0.3% (Low control) 0.8 % (High control) and within run CV of 0.3% (Low control), 0.6% (High control); while HPLC had between run CV of 0.6%(Low control) 1.8% (High control), and within run CV of 0.3% (Low control), and 0.7%. Linear regression analysis displayed high concordance and agreement between the results of both methods.Conclusion: Both methods have comparable results in HbA1c estimation.